2015
DOI: 10.1016/j.algal.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of light and temperature influences on cyanobacterial growth and biohydrogen production

Abstract: Dynamic simulation is a valuable tool to assist the scale-up and transition of biofuel production from laboratory scale to potential industrial implementation. In the present study two dynamic models are constructed, based on the Aiba equation, the improved Lambert–Beer's law and the Arrhenius equation. The aims are to simulate the effects of incident light intensity, light attenuation and temperature upon the photo-autotrophic growth and the hydrogen production of the nitrogen-fixing cyanobacterium Cyanothece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 36 publications
5
42
0
Order By: Relevance
“…This shows, that the FAME production rate always increases with increasing nitrogen quota, while an optimal value exists for light intensity as intense illumination can damage the essential proteins for algal photosynthesis and carbon fixation. Based on the model, the optimal light intensity is identified to be 96 µmol m −2 s −1 , falling within the range of optimal light intensities reported in other publications (Zhang, Dechatiwongse, et al, ). In addition, attention should be paid to the fact that both the local biomass growth rate and the FAME production rate shown in Figure represent instantaneous values, as the location of individual algal cells change continuously as a result of mixing.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…This shows, that the FAME production rate always increases with increasing nitrogen quota, while an optimal value exists for light intensity as intense illumination can damage the essential proteins for algal photosynthesis and carbon fixation. Based on the model, the optimal light intensity is identified to be 96 µmol m −2 s −1 , falling within the range of optimal light intensities reported in other publications (Zhang, Dechatiwongse, et al, ). In addition, attention should be paid to the fact that both the local biomass growth rate and the FAME production rate shown in Figure represent instantaneous values, as the location of individual algal cells change continuously as a result of mixing.…”
Section: Resultssupporting
confidence: 79%
“…Recent studies have concluded that light attenuation is one of the primary limiting factors for biomass cultivation and bioproduct production (Béchet et al, ; Zhang, Dechatiwongse, et al, ). Similar results are obtained in the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings agree with those of Zhang et al (2015), who suggested that light exposure increase can cause considerable damage to the photosynthetic apparatus of cyanobacteria and subsequently lead to a sharp decrease in growth rate. Moreover, in the absence of light, the ability to grow will be reduced, and the cells will eventually die (Dehning and Tilzer 1989).…”
Section: Morphology and Phenotypic Plasticity Under Various Conditionssupporting
confidence: 82%
“…However, for still cultures the light intensity showed a slight incidence. Different authors reported the importance to consider this parameter because it is often found as a limiting factor in culture systems [19] [20]. The efficient air-lift stirring of the glass columns plays a crucial rol for reducing shading between cells, thus allowing to obtain higher values of biomass than in still cultures.…”
Section: Growth and Biomass Productionmentioning
confidence: 99%